PENERAPAN STRATEGI RECIPROCAL TEACHING UNTUK PENINGKATAN PEMAHAMAN KONSEP PESERTA DIDIK PADA PEMBELAJARAN IPS - Hendayani, Santi (STIT AL MULTAZAM, 2018)
This study is aimed to find out the difference of concept comprehension between students who learn by using reciprocal teaching strategy and thoseÂ who study by using lecturing method during social studies learning at 5th grade of SDN Sariwangi in 1st semester of the academic year of 2016/2017. The type of this study is a quasi-experiment with the study design of quasi control group pretest-posttest design. The data of this study is collected through an instrument called a concept comprehension test. This shows that the concept comprehension of social studies of students who learn using reciprocal teaching strategy is better than that of the students who study by using lecturing method. Therefore itÂ proves that reciprocal teaching strategy gives a significant influence on social studies concept comprehension at elementary school. Furthermore the response of the students to ward the implementation of reciprocal teaching strategy is positive. The students feel to have more involvement in the learning process and this method does not make them bored easily. The reciprocal teaching strategy can be a reference of an innovative, creative and effective learning strategy whith is suitable with the students.